2004
DOI: 10.1007/s00276-003-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal neoclassical facial canons in Turkish young adults

Abstract: Four vertical and three horizontal measurements were taken to assess the validity of neoclassical facial canons in 500 (272 female, 228 male) healthy, young adults between the ages of 18 and 25 years from Turkey and to compare them with a different population. The measurements were made by a millimetric compass. The special head height was longer than the special face height in the majority of our group (women/men: 97.8%/91.7%). The three-section facial profile canon was equal in only one male subject (women/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 23 publications
4
44
2
Order By: Relevance
“…For some Turkish adults the eye fissure length was greater (54% of females, 49% of males) than the intercanthal distance. The similar results were also found in Africans (42%) [18] and in another study for Turkish population [3]. In contrast to our findings, Korean American females (100%), Southern Chinese people (100%) and North American white people (52%) have intercanthal distance greater than eye widths [4,6,13].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…For some Turkish adults the eye fissure length was greater (54% of females, 49% of males) than the intercanthal distance. The similar results were also found in Africans (42%) [18] and in another study for Turkish population [3]. In contrast to our findings, Korean American females (100%), Southern Chinese people (100%) and North American white people (52%) have intercanthal distance greater than eye widths [4,6,13].…”
Section: Discussioncontrasting
confidence: 56%
“…Whereas special face height was shorter than the special head height for both males and females in African American and North American white people [6,18,19]. In addition, when we compare our results for canon I with findings that were obtained from other studies in Turkish population the differences were seen between findings [2,3]. The results show that there may be differences in the facial proportions even in different regions of the same country.…”
Section: Discussioncontrasting
confidence: 32%
See 1 more Smart Citation
“…However, reports of anthropometric measurements of the Turkish noses are limited. We have compared our results with the results of other Turkish authors (Uzun et al, 2006;Borman et al, 1999;Hamamci et al, 2010;Bozkir et al, 2004;Gulsen et al, 2006), because some common findings may have been revealed. Also, a comparison was made with the results of different studies made on various races.…”
Section: Discussionmentioning
confidence: 75%
“…After finding the facial image, the left and right eye areas were cropped using the geometric ratios of the face and the left and right eye images were simultaneously found in these areas using parallel tasks [2]. The eye images were combined to obtain a minimum size image containing both eyes.…”
Section: Methodsmentioning
confidence: 99%